Compatibility Between the Indonesian Competition Law and Indonesia’s Climate Change Mitigation Policy Under The UNFCCC Paris Agreement 2016: Quo Vadis? - Arinanto, Satya; Parluhutan, Dian; Sabela, Louise Shania (UI Scholars Hub, 2025)
To overcome the global climate change crisis, the Government of Indonesia (GoI) ratified the United Nations Framework Convention on Climate Change (UNFCCC) Paris Agreement on Climate Change on 22 April 2016, imposing quasi-legal obligations on contracting states to reduce greenhouse gas (GHG) emissions based on Nationally Determined Contribution (NDC) until 2030. As a contracting party of the Paris Agreement, Indonesia has submitted an Enhanced Nationally Determined Contribution (ENDC), increasing its GHG emission reduction target from 31.98 percent to 43.20 percent by 2030. Pillar II of the Golden Indonesia Vision 2045, Indonesia has also reaffirmed its commitment to climate change mitigation nationally and globally to reduce GHG emissions by 34 to 41 percent from the baseline scenario by 2045. Based upon the holistic interpretation of the Indonesian Competition Law Number 5/1999 in conjunction with Article 33 paragraphs (1), (2), and (4) of the Indonesia 1945 Constitution, the Competition Authorities must undertake the sustainability mandate, including climate change mitigation actions, The Indonesian Supervisory Commission for Business Competition (KPPU) in collaboration with other Ministries, the Indonesian Supreme Court (MARI), and the House of Representatives (DPR) must, by the Indonesian Competition Law (Law Number 5/1999), integrate the climate change mitigation policy and environmental preservation endeavours both in the formulation of rules and enforcement measures. The Indonesian competition authorities can, among others, generate the ‘Block Exemptions’ as a discretionary instrument and as a provisional antitrust enforcement policy. A prudent comparative study of competition law and practices in selected jurisdictions reveals that the Indonesian competition authorities can exempt environmentally oriented or sustainability agreements or transactions from traditional prohibitions through five methods, such as the structured rule of reason approach to guarantee the principles of proportionality and accuracy. This study endeavors to provide a feasible contribution to accelerating the climate change mitigation efforts by the government and the stakeholders from the perspective of competition law and practice. In order to enable structured analysis and provide optimal results, this research employs the normative juridical method coupled with a comparative law approach over the European and German competition laws.